2012
DOI: 10.1111/j.1741-3729.2011.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothering While Imprisoned: The Effects of Family and Child Dynamics on Mothering Attitudes

Abstract: Since the early 1990s, the number of children with imprisoned mothers has increased 131%. A mother's imprisonment potentially exposes children to a concentrated disadvantage that undermines their cognitive, emotional, and intellectual abilities. Additionally, such experiences can have deleterious effects on mother‐child relationships, stand‐in caregivers, foster care caseloads, the penal system, and society. Less may be understood, however, about how imprisonment affects the ways in which women view themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Gurusami () found that formerly incarcerated mothers, who faced various obstacles in resuming daily parenting, were under constant pressure to prove to state agencies—social workers and parole or probation officers—that they were fit to have custody of their children. Stringer and Barnes () found that regular contact with their children through letter writing and phone calls helps imprisoned mothers maintain positive views about their role as a parent. More research should investigate parenting strain while in prison and what helps alleviate it.…”
Section: Parenting Minor Children In Social Contextmentioning
confidence: 99%
“…Gurusami () found that formerly incarcerated mothers, who faced various obstacles in resuming daily parenting, were under constant pressure to prove to state agencies—social workers and parole or probation officers—that they were fit to have custody of their children. Stringer and Barnes () found that regular contact with their children through letter writing and phone calls helps imprisoned mothers maintain positive views about their role as a parent. More research should investigate parenting strain while in prison and what helps alleviate it.…”
Section: Parenting Minor Children In Social Contextmentioning
confidence: 99%
“…The physical distance, paired with economic deprivation and the complexity of caretaking relationships for the children of incarcerated mothers, means that very few mothers receive regular visits from their children. For mothers who do receive visits, frequent and flexible communication with children is associated with decreased emotional and psychological distress, as well as decreased parenting stress (Aiello, 2016;Houck & Loper, 2002;Stringer & Barnes, 2012).…”
Section: Mothering While Incarceratedmentioning
confidence: 99%
“…CJ involvement may compound rather than improve health and social vulnerabilities, such that upon reentry women continue to struggle with mental health issues, substance use, family violence, and lack of resources, while also working to resume at least some level of care for their children (Arditti & Few, 2006). Within this context of cumulative disadvantage and family instability, substantial proportions of incarcerated mothers report commitment to their mothering identities and plans to reunify with their children (Enos, 2001; Ferraro & Moe, 2003; Richie, 2001; Stringer & Barnes, 2012). It is unclear from the current body of research in this area how many women do go on to resume care for their children after release from a correctional facility.…”
Section: Multigenerational Effects Of Maternal Incarcerationmentioning
confidence: 99%